Proceedings of the 1st Vietnam Symposium on Advances in Offshore Engineering Energy and Geotechnics - Randolph, M.F.; Doan, Dinh Hong.; Tang, Anh Minh.; Bui, Man.; Dinh, Van Nguyen; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
These proceedings gather a selection of refereed papers presented at the 1st Vietnam Symposium on Advances in Offshore Engineering (VSOE 2018), held on 1-3 November 2018 in Hanoi, Vietnam. The contributions from researchers, practitioners, policymakers, and entrepreneurs address technological and policy changes intended to promote renewable energies, and to generate business opportunities in oil and gas and offshore renewable energy. With a special focus on energy and geotechnics, the book brings together the latest lessons learned in offshore engineering, technological innovations, cost-effective and safer foundations and structural solutions, environmental protection, hazards, vulnerability, and risk management. The book offers a valuable resource for all graduate students, researchers and industrial practitioners working in the fields of offshore engineering and renewable energies.
Offshore Wind Energy: Technology Opportunities and Challenges -- A Philosophy for Developing Offshore Geotechnical Engineering Models -- Offshore Geotechnical Properties, a VR/Neural-interpretation: Part 1 -- Offshore geotechnical Properties, a VR/Neural-interpretation: Part 2 -- An Experimental Evaluation of Characteristics of Ball Penetration Test in Soft Clay -- The Use of Pressuremeters in the Marine Environment -- Application of a Geomechanical Model to Wellbore Stability Analysis -- Investigation on Seepage Erosion and Safety Mechanism of Suction Caisson Installation -- Design of an Offshore Wind Farm Layout -- Research and Development of Wind Power in Vietnam -- Design a Small Direct Drive Wind Power Generator -- Development of Semi Empirical Method for Predicting Axial Pile Capacity -- Reliability Based Installation Design of Suction Caissons in Clay -- Heat Transfer in Gas Hydrate Sediment -- Challenges of Life Extension for Offshore Structures and Foundations.
Keywords: Offshore structures; Energy policy; Energy and state; Geotechnical engineering; Offshore Engineering; Energy Policy, Economics and Management; Geotechnical Engineering and Applied Earth Sciences